2023
DOI: 10.1093/ehjopen/oead073
|View full text |Cite
|
Sign up to set email alerts
|

Association between heart failure and the incidence of cancer: a systematic review and meta-analysis

Abstract: Background The association between heart failure (HF) patients and the incidence of cancer is not well understood, with conflicting results to date. Objective The aim of this meta-analysis was to evaluate whether patients with HF have a higher risk of developing cancer. Material and Methods We performed a systematic literature search using PubMed, Embase, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…59 Galectins act as modulators of tumour progression. 60 SARS-CoV-2 infection lead to many cardiovascular complications and postacute sequelae, 8,9,11,56,61,62 including myocardial inflammation. [63][64][65][66] Many reports point out link between heart failure (HF) and cancer incidence.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Galectins act as modulators of tumour progression. 60 SARS-CoV-2 infection lead to many cardiovascular complications and postacute sequelae, 8,9,11,56,61,62 including myocardial inflammation. [63][64][65][66] Many reports point out link between heart failure (HF) and cancer incidence.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[63][64][65][66] Many reports point out link between heart failure (HF) and cancer incidence. 62,67,68,[68][69][70][71][72][73][74] Systemic inflammatory signals were shown to be promoting cancer. 69 Cancer incidence post COVID is still unclear and our study hints in this direction.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This meta-analysis was conducted and reported following the PRISMA (preferred reporting items for systematic review and meta-analysis) 2020 guidelines and performed according to established methods, as described previously [19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…Translational research has shown an important bidirectional relationship between heart failure (HF) and cancer development, e.g., due to hypoxia, or inflammatory mechanisms. [6][7][8] Clonal hematopoiesis of indeterminate potential (CHIP) is the clonal expansion of mutated hematopoietic stem cells without evidence of hematological malignancy. CHIP has been identified as an independent risk factor for the development and progression of atherosclerotic disease, HF, and adverse outcomes after transcatheter aortic valve repair.…”
Section: Reverse Cardio-oncologymentioning
confidence: 99%